2021
DOI: 10.1016/j.jbc.2021.101230
|View full text |Cite
|
Sign up to set email alerts
|

siRNA screening identifies METTL9 as a histidine Nπ-methyltransferase that targets the proinflammatory protein S100A9

Abstract: A, siRNA screening identifies METTL9 as a histidine N π methyltransferase that targets the pro-inflammatory protein S100A9,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…S100A9 was found to carry histidine methylation at the His107 residue in previous mass spectrum data ( Raftery et al, 1996 ). We and other groups have previously reported that METTL9 methylates S100A9 at the His107 residue ( Daitoku et al, 2021 ; Davydova et al, 2021 ; Lv et al, 2021 ). However, whether METTL9-catalyzed His107 methylation of S100A9 has bona fide physiological functions remains unknown.…”
Section: Dear Editormentioning
confidence: 80%
See 1 more Smart Citation
“…S100A9 was found to carry histidine methylation at the His107 residue in previous mass spectrum data ( Raftery et al, 1996 ). We and other groups have previously reported that METTL9 methylates S100A9 at the His107 residue ( Daitoku et al, 2021 ; Davydova et al, 2021 ; Lv et al, 2021 ). However, whether METTL9-catalyzed His107 methylation of S100A9 has bona fide physiological functions remains unknown.…”
Section: Dear Editormentioning
confidence: 80%
“…1K ). Indeed, His107 methylation of an S100A9 peptide (16 amino acids) showed reduced zinc-binding activity ( Daitoku et al, 2021 ).…”
Section: Dear Editormentioning
confidence: 99%
“…Using tandem "HxH" repeats motif derived from SLC39A7 as a model substrate, we revealed preferred consecutive methylation events catalyzed by METTL9, notably in "C-to-N" direction (Figure 7). Depending on its cognate substrate, METTL9-mediated histidine methylation may regulate many cellular functions, including zinc transport 16 , ER stress 16 , and innate immunity 17 . Functionally, the consecutive and directional catalysis feature of METTL9 may help to determine its substrate preference and regulate corresponding activities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that methylation beyond lysine and arginine is more prevalent than perhaps otherwise considered and should be further investigated in other eukaryotes. In fact, it has recently become apparent that histidine methylation and methyltransferases are prevalent in human ( 58 , 88 91 ). Furthermore, it should be considered that methyltransferases in non-model organisms may catalyze these noncanonical forms of methylation, rather than just lysine and arginine methylation.…”
Section: Why the Yeast Protein Methylation Network Is Near-completementioning
confidence: 99%